Analisis Faktor-Faktor yang Mempengaruhi Hasil Tangkapan Nelayan Payang di Kelurahan Pasie Nan Tigo Kecamatan Koto Tangah Kota Padang: Analysis of Factors Affecting the Catches of Payang Fishermen in Pasie Nan Tigo Village, Koto Tangah District, Padang City - Putri, Eka Soeharno; Arief, Hazmi; Yanti, Chicka Willy (Jurnal Agriuma, 2025)
Payang is one of the fishing gears used by fishermen in Pasie Nan Tigo Village. The utilization of production factors contributes to an increase in the catch of payang fishermen. This study aims to identify the factors influencing the catch of payang fishermen and to determine the scale of their business operations in Pasie Nan Tigo Village. The research employed a survey method with a quantitative descriptive approach. Data were analyzed using multiple linear regression, supported by classical assumption tests and the Cobb-Douglas production function. The results indicate that the production factors significantly influencing the catch of payang fishermen are the duration of fishing trips (X2), the number of settings (net deployments) (X3), and the number of crew members (X4). Meanwhile, the length of the net bag (X1) and the fishermen's work experience (X5) were found to have no significant effect on the catch. The coefficient of determination shows that 75.4% of the variation in catch is explained by the model, while the remaining 24.6% is influenced by other factors not included in the model. The Return to Scale (RTS) value of 1.072 indicates an increasing return to scale, meaning that an increase in input results in a more than proportional increase in output.